The Effect of High Dose Isoflavone Supplementation on Serum Reverse T3 in Euthyroid Men With Type 2 Diabetes and Post-menopausal Women - Sathyapalan, Thozhukat; Köhrle, Josef; Rijntjes, Eddy; Rigby, Alan S.; Dargham, Soha R.; Kilpatrick, Eric S.; Atkin, Stephen L. (Frontiers in Endocrinology, 2018)
Background: The health benefits of soy are widely reported but there are queries on the effect of soy isoflavones on thyroid function and the underlying mechanism of action. Materials and Methods: We examined the effect of soy isoflavones on reverse tri-iodothyronine (or 3,3′,5′-tri-iodothyronine; rT3) in two studies comprising 400 patients: 200 men (study 1; 3 months) and 200 post-menopausal women (study 2; 6 months) who were randomized to consume 15 g soy protein with 66 mg of isoflavones (SPI) daily, or 15 g soy protein alone without isoflavones (SP) daily. Results: SPI supplementation increased rT3 serum concentration in both men 0.41 (0.12) vs. 0.45 (0.14) nmol/L and women 0.33 (0.12) vs. 0.37 (0.09) nmol/L at 3 months compared to SP that was not seen at 6 months. Thyroid stimulating hormone (TSH) serum concentrations increased while free thyroxine (fT4) concentrations decreased with 3 months of SPI compared to SP supplementation for both men and women. rT3 correlated with TSH in both studies (p = 0.03) but not with either fT3 or fT4. fT3 levels did not differ between the SPI and SP preparations. Conclusion: Soy isoflavones transiently increased rT3 levels within 3 months though reverted to baseline at 6 months. The mechanism for this would be either rT3 degrading deiodinase 1 and/or deiodinase 2 activities are transiently inhibited at 3 months, or inhibition of deiodinase 3, which generates rT3 from T4 is induced at 6 months. These changes were mirrored in the TSH concentrations, suggesting that short-term high dose isoflavone transiently impairs thyroid function in the first 3 months and may impact on general health during this period. ISRCTN Registry: ISRCTN 90604927; ISRCTN34051237.